Kryteria elitarności szkół w świadomości społecznej różnych kategorii osób = Criteria of school elitism in the social consciousness of different categories of people - Kołodziejska, Elżbieta; Mianowska, Edyta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This study analyses the perception of school elitism criteria among working adults, students and pupils from Zielona Gora. These researches are the first stage of a Project leading to a comparison of teaching results of elite schools and ordinary schools. Respondents were questioned about elite school features they could name in order to find the existing social criteria of school elitism and compare them to the criteria used in the official school ranking. There are presented four groups of features which can be indicators of an elite school. The study also reveals that pupils, students and working adults have different attitudes to school elitism.
Keywords: szkolnictwo polskie; elitarność; badania społeczne; badania sondażowe